Kesejahteraan dan Semangat Kerja: Kajian Kompensasi dan Motivasi pada Paramedis Honorer - Amiroh Ulfa; Ade Ria Nirmala (Al-Manar Journal of Accountancy and Business Studies, 2025)
This study aims to analyze the effect of compensation and motivation on job satisfaction of honorary paramedics at Bhayangkara Hospital Class III Pekanbaru. The phenomenon of job dissatisfaction among honorary workers, especially those related to limited compensation and low work motivation, is an important background in this study. This study uses a quantitative approach with a survey method, where the entire population of 86 people is sampled through a total sampling technique. Data collection was carried out through a closed questionnaire with a Likert scale, and data analysis was carried out using multiple linear regression with the help of SPSS software version 25. The results of the study indicate that both compensation and motivation partially and simultaneously have a positive and significant effect on job satisfaction of honorary paramedics. The partial test shows a significance value below 0.05 for both variables, while the simultaneous test (F-test) shows that compensation and motivation together affect job satisfaction by 57.7% (R2 = 0.577), the rest is influenced by other factors outside this study. These findings emphasize the importance of improving the compensation system and strengthening work motivation to improve job satisfaction and the quality of hospital health services.